Packaging method of battery with nickel-based surface
By first applying an acrylic resin to the nickel-based surface to form a first layer of polymer material and then applying a thermosetting polymer material, the bonding strength problem of the nickel-based surface packaging material is solved, adhesion in the cohesive failure mode is achieved, and the mechanical stability and heat resistance of the electrical components are enhanced.
Patent Information
- Application Number
- CN202480012132.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-13
- Filing Date
- 2024-02-08
- Publication Date
- 2025-09-19
AI Technical Summary
It is difficult to achieve good adhesion and high adhesion strength with nickel-based surfaces with existing technologies, especially in the case of an adhesion failure mode that is prone to occur between the packaging material and the nickel-based surface.
A two-step encapsulation method is used, where an acrylate resin is used to form the first layer of polymer material, followed by the application of a thermosetting polymer material to form a cohesive failure mode bond.
The bonding strength between the packaging material and the nickel-based surface is improved, the bonding failure mode is avoided, and the mechanical stability and heat resistance of the electrical components are enhanced.
Smart Images

Figure BDA0005542662690000182 
Figure BDA0005542662690000191
Abstract
Description
Technical Field
[0001] The present invention relates to a novel method for encapsulating articles with nickel-based surfaces, particularly electrical components with nickel-based surfaces, using a thermosetting polymer as the encapsulating material. The method of the present invention is based on applying a first coating based on an acrylic polymer material between the article with the nickel-based surface and the encapsulating material. The present invention also relates to a material kit for encapsulating articles with nickel-based surfaces and the articles obtained by such encapsulation. Background Art
[0002] From power generation and electronics to automotive manufacturing, nickel and nickel-based alloys play a vital role in our economy. Nickel and nickel-based alloys possess exceptional properties and are widely used in the assembly of a wide range of products, including battery components, electronic wires, and mobile phones. These components can be provided with a nickel layer to protect against corrosion and wear and to improve contact resistance.
[0003] Generally speaking, potting and / or encapsulation techniques are often applied in these applications to protect components and optimize their performance. Potting is the process of partially or completely filling or embedding a component or assembly within a housing with a resin. Encapsulation is a similar process to potting, but differs in that the component is typically immersed in a mold filled with resin, rather than necessarily filling the entire mold cavity.
[0004] Resin systems used to encapsulate electrical components need to meet various properties, such as good adhesion, heat resistance, and insulation. The most common types of resins used as encapsulants are polyurethanes, acrylics, epoxies, and silicones.
[0005] Encapsulating electrical components with these specialized polymer materials prevents thermal runaway and heat propagation, reduces mechanical shock and vibration under normal use conditions, and creates a seal against moisture, solvents, and corrosion. These enhancements ensure greater safety, higher mechanical stability, and improved long-term performance.
[0006] However, a potential problem is that polymers struggle to bond well to the nickel and nickel-based alloys that make up the surfaces of electrical components, particularly batteries. Nickel is an inherently inert material and tends to be smooth, resulting in a small effective surface area. Therefore, components with primarily nickel surfaces can only be bonded together using adhesives, which is a difficult task.
[0007] To improve the adhesion of adhesive layers to nickel surfaces, surface pretreatments have been proposed. US Pat. No. 5,532,024 describes a method for improving the adhesion of polymer materials to nickel surfaces by treating the substrate with H₂O₂ at temperatures above 40°C. This method has the disadvantages of being a wet process, which is time-consuming and requires high temperatures, which can damage electrical components in some cases.
[0008] DE 102017202851 describes a method for improving the adhesion of polymer materials to nickel surfaces by treating the substrate with plasma or heat. However, plasma treatment is not effective under all conditions because it can negatively impact other components connected to the substrate being bonded. Furthermore, while plasma treatment may improve adhesion values in certain situations, it does not necessarily result in a cohesive failure mode.
[0009] These prior art methods are not feasible for encapsulating batteries with nickel-based surfaces in thermally conductive resins.
[0010] In view of these technical problems, the applicant has found that there is a need to improve the adhesion of encapsulating materials to nickel-based surfaces.
[0011] Therefore, the object of the present invention is to provide materials and methods for electronic component packaging, in particular for battery packaging, that achieve good adhesion properties and high bond strength to nickel-based surfaces. In this context, improved adhesion primarily refers to achieving a cohesive failure mode in which the bond between the packaging material and the nickel-based surface of the electronic component is forcibly broken.
[0012] The applicant has surprisingly found that by combining at least two encapsulating materials, a cohesive failure mode can be obtained between the encapsulating material and the nickel-based surface, whereas both materials alone would fail in an adhesive failure mode.
[0013] The method of the present invention consists in applying a first layer of a polymer material (P) and a second top layer of an encapsulating material (A) on an article with a nickel-based surface, wherein the polymer material (P) adheres better to the nickel-based surface than the material (A), but does not meet the numerous requirements required for encapsulating electronic components, wherein the material (A) adheres so well to the polymer material (P) that cohesive failure occurs in the layer of the material (A). Summary of the Invention
[0014] The present invention relates to a method for encapsulating an article having a nickel-based surface (S) with a thermosetting polymer material (A), said method comprising at least the following steps:
[0015] i) coating at least a portion of the surface (S) of the article with a first curable resin composition;
[0016] ii) at least partially curing the first curable resin composition to obtain a nickel-based article coated with a first layer of polymeric material (P);
[0017] iii) applying at least a precursor composition of a thermosetting polymer material (A) on the first layer of polymer material (P);
[0018] iv) curing the precursor composition to obtain a top layer of thermosetting polymer material (A),
[0019] wherein the first curable resin composition is selected from acrylate resins and methacrylate resins, and wherein the thermosetting polymer material (A) comprises a polymer having the following properties: Tg is less than or equal to -10°C, a tensile strength after curing of 0.5-20 MPa, the tensile strength is measured according to method ISO 527, and an elongation at break after curing of 5-250%, the elongation at break is measured according to method ISO 527.
[0020] Preferably, the nickel-based surface (S) of the article is a solid nickel surface, a nickel-plated surface or a nickel-coated surface.
[0021] Preferably, the first curable resin composition is a two-part composition comprising at least: a) a polymerizable monomer composition comprising an acrylate or methacrylate or a derivative thereof, and b) at least one initiator.
[0022] Preferably, the polymerizable monomer composition a) further comprises at least one acid, preferably selected from acrylic acid, methacrylic acid, vinylacetic acid, acryloxypropionic acid, maleic acid and crotonic acid, and / or at least one acid ester, preferably a phosphoric acid ester.
[0023] According to a first embodiment, the thermosetting polymeric material (A) is a polyurethane, and the precursor composition of said thermosetting polymeric material (A) is a two-part composition comprising at least a) a polyol component and b) an isocyanate component.
[0024] According to a second embodiment, the thermosetting polymer material (A) is an epoxy resin, and the precursor composition of said thermosetting polymer material (A) is a two-part composition comprising at least a) an epoxy compound and b) a curing agent.
[0025] Preferably, the precursor composition of the thermosetting polymer material (A) of the first or second embodiment further comprises a filler, preferably at least 30 wt% of a filler.
[0026] Preferably, the precursor composition of the thermosetting polymer material (A) of the first or second embodiment further comprises one or more additives selected from the group consisting of dyes, pigments, flame retardants, softeners, heat aging stabilizers and thixotropy modifiers or rheology modifiers.
[0027] Preferably, in steps i) and iii), the first curable resin composition and the precursor composition of the thermosetting polymer material (A) are applied to the nickel-based article surface (S), respectively, in an amount providing a dry film thickness of 0.1-3 mm.
[0028] Preferably, in steps ii) and iv), the first curable resin composition and the second curable resin composition are cured at ambient temperature, respectively.
[0029] According to another aspect, the present invention relates to a kit for packaging an article with a nickel-based surface (S), said kit comprising:
[0030] i) a first curable resin composition selected from acrylate resins and methacrylate resins;
[0031] ii) a precursor composition of a thermosetting polymer material (A), wherein the thermosetting polymer material comprises a polymer having the following properties: a Tg lower than or equal to -10°C, a tensile strength after curing of 0.5 to 20 MPa, the tensile strength being measured according to method ISO 527, and an elongation at break after curing of 5 to 250%, the elongation at break being measured according to method ISO 527.
[0032] According to another aspect, the present invention relates to a device comprising a packaged article, said device being produced by carrying out the method of the present invention. Preferably, said article is selected from batteries with a nickel-based surface.
[0033] According to another aspect, the present invention relates to a method for producing an electrical and electronic insulating device, wherein said method comprises at least one step of implementing the method for encapsulating an article as described above and in more detail below.
[0034] According to another aspect, the present invention relates to the use of a combination of a polymer material (P) and a thermosetting polymer material (A) for encapsulating one or more electrical components, in particular batteries, with a nickel-based surface (S) in a method as defined above and described in detail below, in order to improve the resistance of the packaged assembly to thermal cycles, prevent thermal runaway and heat propagation, and / or reduce mechanical shocks and vibrations. DETAILED DESCRIPTION
[0035] The term "consisting essentially of" followed by one or more characteristics means that in addition to the components or steps specifically listed, components or steps that have no material effect on the properties and characteristics of the invention may also be included in the methods or materials of the invention.
[0036] Unless expressly stated otherwise, the phrase "between X and Y" is inclusive. This phrase means that the intended range includes the values of X and Y and all values between X and Y.
[0037] For purposes of the present invention, the terms "potting" and "encapsulation" are used interchangeably to describe the process of coating electronic components, particularly batteries, with resins to protect them from potential environmental threats, according to methods well known in the art.
[0038] For the purposes of the present invention, "thermosetting polymeric material" refers to a polymer that cures or solidifies into a hard shape upon application of a curing method such as heat or radiation. The curing process is irreversible as it introduces a polymer network cross-linked by covalent chemical bonds.
[0039] "Curable composition" refers to a composition comprising one or two components or prepolymers, the curing of which results in a chemical reaction that produces extensive crosslinking between polymer chains, thereby forming an infusible and insoluble solid polymer network. The curing can be initiated by heat, radiation, or chemical additives.
[0040] As used herein, the term "ambient temperature" refers to the temperature of the surrounding working environment (e.g., the temperature of the area, building, or room where the curable system is applied or produced), excluding any temperature changes caused by chemical reactions. Ambient temperature is typically about 10-30°C, more specifically about 25°C. "Ambient temperature" is used interchangeably with "room temperature" herein.
[0041] For purposes of this invention, the term "Tg" refers to the glass transition temperature. Below this temperature, an amorphous material behaves as a glassy solid, while above this temperature, the same material behaves as a liquid or rubbery solid. Tg can be measured using a variety of techniques, including differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), and thermomechanical analysis (TMA).
[0042] For purposes of this invention, adhesion failure is defined as follows: failure occurs when the encapsulant releases from the nickel-based surface but does not tear or separate when the article is subjected to load, fails or loses adhesion, i.e., failure occurs at the interface between the encapsulant and the nickel-based surface of the article.
[0043] For purposes of this invention, cohesive failure is defined as failure occurring in the bulk layer of the encapsulant when the article is subjected to load, fails, or loses adhesion, with a portion of the encapsulant remaining on the encapsulant and a portion remaining on the nickel-based surface of the article.
[0044] Packaging method for products with nickel-based surface
[0045] According to a first aspect, the present invention relates to a method for encapsulating an article having a nickel-based surface (S) with a thermosetting polymer material (A), said method comprising at least the following steps:
[0046] i) coating at least a portion of the surface (S) of the article with a first curable resin composition,
[0047] ii) at least partially curing the first curable resin composition to obtain a nickel-based article coated with a first layer of polymeric material (P);
[0048] iii) applying at least a precursor composition of a thermosetting polymer material (A) on the first layer of polymer material (P);
[0049] iv) curing the precursor composition to obtain a top layer of thermosetting polymer material (A),
[0050] wherein the first curable resin composition is selected from acrylate resins and methacrylate resins, and wherein the thermosetting polymer material comprises a polymer having the following properties: Tg is less than or equal to -10°C, a tensile strength after curing of 0.5-20 MPa, preferably 1-10 MPa, the tensile strength being measured according to method ISO 527, and an elongation at break after curing of 5-250%, preferably 5-100%, the elongation at break being measured according to method ISO 527.
[0051] The applicant has found that the adhesion between the thermosetting polymeric material (A) and the nickel surface of the article can be improved by applying a coating of a polymeric material (P) of an acrylate resin before applying the thermosetting polymeric material (A).
[0052] Acrylates are known to adhere better, but not perfectly, to nickel-based surfaces. However, these polymers fail to meet the extensive requirements required for electrical component encapsulation and often fail in an adhesive failure mode.
[0053] Specifically, the applicant surprisingly discovered that by combining two materials (A) and (P) that would fail in an adhesive failure mode when used alone, the failure mode of the joint between the thermosetting polymer material (A) and the surface of the nickel-based article can be made a cohesive failure mode in the thermosetting polymer material (A).
[0054] Nickel-based product surface (S)
[0055] In the context of the present invention, "nickel-based surface" refers to a surface of an article that primarily contains nickel. Preferably, the surface comprises at least 50 wt%, preferably at least 70 wt%, more preferably at least 90 wt%, most preferably 100 wt% nickel.
[0056] The surface of the article used in the method of the present invention can generally be any form of nickel, including pure nickel and nickel-based alloys.
[0057] For example, nickel-based alloys may include nickel-phosphorus alloys, nickel-iron alloys, nickel-copper alloys, nickel-molybdenum alloys, nickel-chromium alloys, nickel-chromium-iron alloys, nickel-chromium-molybdenum alloys, and nickel-titanium alloys.
[0058] The nickel-based surface of the product used in the method of the present invention can also be a solid nickel surface, a nickel-plated surface or a nickel-covered surface. Nickel can be plated or covered on any suitable metal substrate, including for example copper, aluminum, aluminum alloy, iron or steel.
[0059] According to a preferred embodiment of the present invention, the nickel-based surface of the article is a nickel-plated surface or a nickel-coated surface.
[0060] "Nickel-plated surface" means that the metal surface has been treated with a thin layer of nickel to prevent oxidation. Nickel plating can be achieved by electroplating, which requires an electric current, or by electroless plating, which is an autocatalytic chemical process, including any conventional method, such as using nickel (II) hypophosphite or nickel borate. "Nickel-coated surface" means that the metal surface has been treated with a thin layer of nickel to prevent oxidation by hot-dip methods known in the art.
[0061] Nickel surfaces are preferably nickel-plated steel. Examples of this type of surface are Commercially available.
[0062] Preferably, the article used in the method of the invention is a battery, in particular a battery with a nickel surface, preferably a surface made of nickel-plated steel.
[0063] Alternatively, the article to be used in the process of the invention may be selected from the group consisting of rotors or stators of electric machines such as electric motors or generators, (power) electronic components, batteries, switch rings of electric motors, switchgear, printed circuit boards, bushings, transformers, dry-type transformers, instrument transformers, metal inserts embedded in insulating structural materials.
[0064] First curable resin composition and polymer material (P)
[0065] The present invention relies on applying a layer of polymeric material (P) to an article having a nickel-based surface (S) before applying a thermosetting polymer (A) as encapsulating material.
[0066] The polymer material (P) layer is obtained by applying a first curable resin composition to the surface of the article and then at least partially curing the composition to form a solid layer.
[0067] The first curable resin composition is preferably in a liquid state prior to curing and does not cure within the time necessary for application to the surface of the article.
[0068] The first curable resin composition preferably comprises a two-part composition including a polymerizable monomer composition comprising an acrylate or methacrylate or a derivative thereof, and an initiator including a free radical generator to effect crosslinking upon mixing of the two parts.
[0069] A "two-part composition" refers to a composition comprising two components as a two-packaging system (or kit) designed for extemporaneous mixing of the two components shortly before curing. When the two components are mixed / blended together and cured, they may form a cured solid coating or layer by forming chemical bonds (called crosslinking) between the two components.
[0070] Preferably, the polymerizable monomer composition comprises an acrylate or methacrylate selected from the group consisting of methyl methacrylate, methyl acrylate, butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, ethyl acrylate, isobornyl methacrylate, isobornyl acrylate, 2-hydroxyethyl methacrylate, glycidyl methacrylate, tetrahydrofurfuryl methacrylate, acrylamide, n-methylacrylamide, and mixtures thereof. Other examples include acrylates or methacrylates containing monofunctional or polyfunctional monomers other than hydroxyl groups, such as amide, cyano, chloro, and silane substituents.
[0071] The derivatives of acrylates or methacrylates can advantageously be selected from the group consisting of: a) esters of acrylic acid and / or methacrylic acid with monohydric, dihydric and polyhydric alcohols, b) esters of acrylic acid and / or methacrylic acid with hydroxyl-functional polyethers, c) esters of acrylic acid and / or methacrylic acid with hydroxyl-functional polyesters, d) esters of acrylic acid and / or methacrylic acid with hydroxyl-functional cycloaliphatic and aromatic compounds. These derivatives may contain other polymerizable functional groups.
[0072] According to a preferred embodiment of the present invention, the acrylate or methacrylate is selected from ethyl acrylate, methyl acrylate, methyl methacrylate and butyl methacrylate, preferably methyl methacrylate.
[0073] Preferably, the polymerizable monomer composition further comprises at least one acid and / or at least one acid ester.
[0074] Suitable acids can include ethylenically unsaturated mono- or polycarboxylic acids, such as acrylic acid, methacrylic acid, vinyl acetic acid, and acryloyloxypropionic acid. Acids can also include maleic acid and crotonic acid. In addition, compounds having at least one strong acid active hydrogen group or at least one phosphonic acid active hydrogen group, such as hydroxyethyl diphosphonic acid, phosphonic acid, and derivatives thereof, or oligomers or polymer structures having phosphonic acid functional groups or similar acid strength functional groups are also included.
[0075] The acid is preferably acrylic acid, methacrylic acid or a mixture thereof.
[0076] Suitable acid esters include phosphates, sulfonates, and mixtures thereof.
[0077] Examples of suitable phosphates are 2-hydroxyethyl methacrylate phosphate (HEMA phosphate) and bis[2-(acryloyloxy)ethyl] hydrogen phosphate.
[0078] According to a preferred embodiment of the present invention, the polymerizable monomer composition comprises 2-hydroxyethyl methacrylate phosphate (HEMA phosphate) and / or methacrylic acid and / or acrylic acid.
[0079] Preferably, the polymerizable monomer composition comprises 0.1-20 wt%, preferably 0.2-10 wt%, more preferably 0.5-5 wt% of the above acid and / or acid ester.
[0080] Preferably, the polymerizable monomer composition comprises 0.5-20 wt%, preferably 1-15 wt% of the above-mentioned acids, preferably methacrylic acid and / or acrylic acid.
[0081] Preferably, the polymerizable monomer composition comprises 0.1-10 wt%, preferably 0.1-5 wt% of the above-mentioned phosphate ester, preferably 2-hydroxyethyl methacrylate phosphate (HEMA phosphate) and / or bis[2-(acryloyloxy)ethyl] hydrogen phosphate.
[0082] The initiators used in the present invention are known in the art. Examples of initiators used in the present invention include peroxides, hydroperoxides, peresters, peracids and azo compounds. Representative examples of peroxides and hydroperoxides include, but are not limited to, benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, dicumyl peroxide, tert-butyl peroxyacetate, tert-butyl perbenzoate and combinations thereof.
[0083] Preferably, the initiator is selected from peroxides, hydroperoxides and mixtures thereof.
[0084] Preferably, the weight ratio of the polymerizable monomer composition portion to the initiator portion is from about 20:1 to about 1:1.
[0085] Preferably, the first curable composition further comprises other additives, such as epoxy resin, toughening agent (core shell, rubber), plasticizer, colorant, viscosity control agent, etc. These additives can be included in the polymerizable monomer composition part and / or the initiator part.
[0086] According to a preferred embodiment of the present invention, the first curable composition is selected from the group consisting of the following commercially available compositions from Huntsman 2051 and 2050.
[0087] Preferably, in step i) of the method of the present invention, the first curable resin composition is at least partially applied to the surface of the article in a thickness of 0.05 to 1 mm, preferably 0.1 to 0.2 mm.
[0088] Preferably, the layer of the first curable resin composition has a regular thickness over all surfaces of the article to which it is applied.Preferably, the layer of the first curable resin composition is applied over the entire surface of the article to be encapsulated.
[0089] The application of the first curable resin composition layer can be carried out by any method known to those skilled in the art, such as spraying, dipping, painting, spin coating, and the like.
[0090] According to a most preferred embodiment, the nickel-based surface (S) of the article is cleaned and preferably dried before applying the first curable resin composition. Preferably, the surface of the nickel-based surface (S) is cleaned with isopropyl alcohol.
[0091] Preferably, in step ii) of the process of the present invention, the first curable resin composition is at least partially cured at ambient temperature, in particular at a temperature of 10-30°C, preferably at a temperature of 23°C, thereby forming a solid layer of polymer material (P).
[0092] Preferably, the first curable resin composition is at least partially cured for a time interval of 15 minutes to 96 hours, preferably 30 minutes to 72 hours, more preferably 60 minutes to 48 hours to form a solid layer of polymeric material (P).
[0093] According to one embodiment, in step ii) of the process of the invention, the first curable resin composition is fully cured before applying the precursor composition of the thermosetting polymer material (A) in step iii).
[0094] Preferably, the glass transition temperature Tg of the polymer material (P) layer obtained after curing is 60-170°C, preferably 90-150°C, more preferably 110-140°C.
[0095] Preferably, the layer of polymer material (P) obtained after curing has an elongation at break measured according to ISO 527 using a sample of 1 mm thickness of 5-20%, preferably 5-15%.
[0096] Preferably, the polymer material (P) layer obtained after curing has a tensile strength of 10-70 MPa, preferably 15-60 MPa, more preferably 20-50 MPa, measured according to ISO 527. The tensile strength is measured according to ISO 527. In particular, the tensile strength of the polymer material (P) of the present invention is higher than the tensile strength of the thermosetting polymer material (A).
[0097] Precursor composition of thermosetting polymer material (A) and thermosetting polymer material (A):
[0098] In step iii) of the process according to the invention, the surface of the coated, at least partially cured article obtained in step ii) is encapsulated in a known manner with a precursor composition of a thermosetting polymeric material (A).
[0099] According to the present invention, the precursor composition of the thermosetting polymer material (A) comprises a polymer having the following properties: a glass transition temperature Tg lower than or equal to -10°C, preferably from -50°C to -10°C, more preferably from -50°C to -40°C, an elongation at break measured according to ISO 527 of 5-250%, preferably 5-100%, and a tensile strength measured according to ISO 527 of 0.5-20 MPa, preferably 1-10 MPa.
[0100] Preferably, the precursor composition of the thermosetting polymer material (A) comprises a polymer having a tensile modulus measured according to ISO 527 of 10 to 100 MPa.
[0101] Preferably, the precursor composition of the thermosetting polymer material (A) comprises a polymer having a thermal conductivity of 0.1-2 W / m*K.
[0102] Preferably, the thermosetting polymer material (A) used in the method of the present invention is selected from polyurethanes, epoxy resins and mixtures thereof. According to a preferred embodiment of the present invention, the thermosetting polymer material (A) is polyurethane.
[0103] According to a first embodiment, the precursor composition of the thermosetting polymeric material (A) is a curable two-part resin system comprising:
[0104] (a) comprising at least a first portion of a polyol compound, and
[0105] (b) a second portion comprising at least an isocyanate compound.
[0106] Optionally, according to this embodiment, the precursor composition of the thermosetting polymeric material (A) comprises one or more fillers as a component of the first part or the second part.
[0107] According to a first embodiment, the precursor composition of the thermosetting polymer material (A) may also comprise in the first or second part one or more additives selected from the group consisting of dyes, pigments, flame retardants, softeners, heat aging stabilizers and thixotropy modifiers or rheology modifiers.
[0108] Polyol compounds
[0109] Non-limiting examples of suitable polyols for use in the present invention can include, but are not limited to, polyether polyols, polyester polyols, polycaprolactone polyols, polycarbonate polyols, polyurethane polyols, polyvinyl alcohol, polymers of hydroxyl-functional acrylates, polymers of hydroxyl-functional methacrylates, polymers containing allyl alcohols, and mixtures thereof.
[0110] According to a preferred embodiment, the polyol compound is selected from polyether polyols and polyester polyols.
[0111] Examples of polyester polyols include those obtained by reacting a polyol with a polyacid. The polyol may be selected from, for example, ethylene glycol, polyethylene glycol, butanediol, polybutylene glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, and 2-methyl-1,8-octanediol. The polyacid may be selected from, for example, phthalic acid, dimer acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, adipic acid, sebacic acid, and the like.
[0112] The polyether polyols can be selected from polyether polyols based on ethylene oxide, polyether polyols based on propylene oxide, corresponding ethylene oxide / propylene oxide copolymers (which can be random copolymers or block copolymers) and mixtures of these polyether polyols. The ratio of ethylene oxide to propylene oxide in the ethylene oxide / propylene oxide copolymers can vary within wide ranges, as is well known to the skilled person.
[0113] According to a preferred embodiment, the polyol compound is selected from polyether polyols.
[0114] Isocyanate compounds
[0115] Isocyanate components useful in the present invention are well known in the art and are organic compounds containing two or more isocyanate groups per molecule. The isocyanate component can be aromatic, cycloaliphatic or aliphatic, and can be monomeric or oligomeric.
[0116] Preferably, the NCO functionality of the isocyanate component is greater than or equal to 2, preferably 2-3.
[0117] "Isocyanate functionality" refers to the number of reactive NCO groups per molecule of an isocyanate molecule or polymeric isocyanate. For example, most polyisocyanates, particularly MDI-type polyisocyanate compounds, contain a mixture of monomeric and polymeric MDI, and the isocyanate functionality is the average functionality of the different molecular and polymeric species.
[0118] According to the present invention, suitable isocyanate compounds used in the precursor composition of the thermosetting polymer material (A) can be selected from dodecane-1,12-diisocyanate, 2-ethyltetramethylene-1,4-diisocyanate, 2-methylpentamethylene-1,5-diisocyanate, tetramethylene-1,4-diisocyanate, hexamethylene-1,6-diisocyanate (HMDI), cyclohexane-1,3-diisocyanate, cyclohexane-1,4-diisocyanate, isophorone diisocyanate (IPDI), hexahydrotoluene-2,4-diisocyanate, hexahydrotoluene-2,5-diisocyanate, Dicyclohexylmethane-2,2′-diisocyanate, dicyclohexylmethane-4,4′-diisocyanate, dicyclohexylmethane-2,4′-diisocyanate, toluene-2,4-diisocyanate (2,4-TDI), toluene-2,6-diisocyanate (2,6-TDI), diphenylmethane-2,2′-diisocyanate (2,2′-MDI), diphenylmethane-4,4′-diisocyanate (4,4′-MDI), diphenylmethane-2,4′-diisocyanate (2,4′-MDI), polyphenylpolymethylene polyisocyanate (crude MDI) and mixtures thereof.
[0119] As used herein, "MDI" refers to methylene diphenyl diisocyanate, also known as diphenylmethane diisocyanate, and its isomers. MDI exists as one of three isomers (4,4'-MDI, 2,4'-MDI, and 2,2'-MDI), or as a mixture of two or more of these isomers. Unless otherwise specified, "MDI" may also refer to and include polymeric MDI. Polymeric MDI is a compound having a chain of three or more benzene rings interconnected by methylene bridges, each of which has an isocyanate group attached to it.
[0120] Preferably, the mass ratio between the polyol compound and the isocyanate component in the precursor composition of the thermosetting polymer material (A) is 20:1 to 1:1, preferably 20:1 to 5:1.
[0121] filler
[0122] Preferably, the filler that may be included in the precursor composition of the thermosetting polymer material (A) is chosen from mineral fillers or metal powders.
[0123] Preferably, the filler is an inorganic filler selected from the following: quartz sand, quartz powder, silicon dioxide, amorphous silicon dioxide, fused silica, aluminum oxide, titanium oxide, zirconium oxide, Mg(OH)2, Al(OH)3, dolomite [CaMg(CO3)2], AlO(OH), silicon nitride, boron nitride, aluminum nitride, silicon carbide, boron carbide, chalk, calcium carbonate, barite, gypsum, hydromagnesite, zeolite, talc, mica, kaolin and wollastonite, aluminosilicate, aluminum silicate, ground glass, glass beads. The filler may optionally be silanized. The filler is preferably Al(OH)3.
[0124] Preferably, the precursor composition of the thermosetting polymer material (A) comprises at least 30 wt% or more, preferably 40 wt% or more, more preferably 50 wt% or more of a filler, preferably an inorganic filler, relative to the total weight of the composition.
[0125] According to a second embodiment, the precursor composition of the thermosetting polymeric material (A) is a curable two-part resin system comprising:
[0126] (a) a first part comprising at least one epoxy resin, and
[0127] (b) A second part comprising at least one curing agent.
[0128] Optionally, according to a second embodiment, the precursor composition of the thermosetting polymer material (A) comprises one or more fillers as a component of the first part or the second part.
[0129] The precursor composition of the thermosetting polymer material (A) according to the second embodiment may also contain one or more additives selected from the group consisting of dyes, pigments, flame retardants, softeners, heat aging stabilizers and thixotropy modifiers or rheology modifiers in the first part or the second part.
[0130] Epoxides
[0131] The epoxy compound used in the method of the present invention is a compound containing at least one vicinal epoxy group. The epoxy compound may be saturated or unsaturated, aliphatic, cycloaliphatic, aromatic or heterocyclic, and may also be substituted. The epoxy compound may be a monomer or a polymer.
[0132] Preferably, the epoxy component is prepared by methods known in the art, in particular by reacting epichlorohydrin with a compound comprising at least one phenolic compound under alkaline conditions, for example in an alkaline reaction medium or in the presence of a suitable base.
[0133] Examples of suitable epoxy resins include, but are not limited to, butanediol diglycidyl ether, hexanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, hexahydrophthalic acid diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol polyglycidyl ether, neopentyl glycol diglycidyl ether, or mixtures thereof.
[0134] According to a preferred embodiment, the epoxy compound is selected from the group consisting of diglycidyl ethers of bisphenol A and polyglycidyl ethers of novolacs. Examples of such epoxy components include, but are not limited to, those available from Shell 826 and DPL-862 and DEN 439 and DEN 438 available from Dow Chemical Co.
[0135] Optionally, the epoxy component may further comprise an aqueous organic solvent or diluent present in an amount effective to reduce the viscosity of the system and thereby improve processing properties. Examples of diluents include ketones, alcohols, and glycol ethers.
[0136] curing agent
[0137] Suitable curing agents for epoxy resin compositions include, but are not limited to, amines, amides, anhydrides, phenols, and thiols.
[0138] Preferably, the curing agent is liquid at ambient temperature and can be mixed with the epoxy compound without heating.
[0139] The curing agent is preferably an amine-based curing compound selected from aliphatic amines such as ethylenediamine, diethylenetriamine, triethylenetetramine, isophoronediamine, and aromatic amines such as diaminodiphenylmethane (DDM).
[0140] The amount of curing agent used must be sufficient to achieve complete curing. The amount of curing agent used in the second curable composition is such that the ratio of amine hydrogen equivalents to epoxy equivalents can be in the range of 0.9 to 1.5, preferably 0.9 to 1.1, and more preferably 1.
[0141] The precursor composition of the thermosetting polymer material (A) can be prepared in a conventional manner, in particular by mixing and / or blending the two-part resin system described above in accordance with the first or second embodiment, optionally with the addition of one or more fillers, and then applied to the surface of the article already coated with the layer of polymer material (P). For example, the application can be carried out by dipping, trickle impregnation, vacuum pressure impregnation and / or casting onto the article.
[0142] The precursor composition of the thermosetting polymer material (A) is preferably in liquid form before curing and does not cure within the time necessary for application to the layer of polymer material (P).
[0143] The precursor composition of the thermosetting polymer material (A) preferably has a sufficiently low viscosity. Preferably, the viscosity of the precursor composition of the thermosetting polymer material (A) before curing is 0.5-10 centipoise, preferably 0.5-6 centipoise.
[0144] Preferably, in step iii) of the process of the present invention, the precursor composition of the thermosetting polymer material (A) is applied to the layer of polymer material (P) in a thickness of 0.05 to 1 mm, preferably 0.1 to 0.2 mm.
[0145] Preferably, the first layer of polymeric material (P) and the top layer of thermosetting polymeric material (A) are applied to the nickel-based article surface (S) in an amount providing a total dry film thickness of 0.1-2 mm, preferably 0.2-0.4 mm.
[0146] The thermosetting polymer material (A) is prepared by curing a precursor composition of the thermosetting polymer material (A).
[0147] Preferably, the curing temperature of the precursor composition of the thermosetting polymer material (A) is 10-35°C, preferably 15-30°C, advantageously about 23°C.
[0148] Preferably, the curing time of the precursor composition of the thermosetting polymer material (A) is 15 minutes to 96 hours, preferably 30 minutes to 72 hours, more preferably 60 minutes to 48 hours, thereby forming a solid layer of the thermosetting polymer material (A).
[0149] filler
[0150] Preferably, the filler that may be included in the precursor composition of the thermosetting polymer material (A) according to the second embodiment is chosen from mineral fillers or metal powders.
[0151] Preferably, the filler is an inorganic filler selected from the following: quartz sand, quartz powder, silicon dioxide, amorphous silicon dioxide, fused silica, aluminum oxide, titanium oxide, zirconium oxide, Mg(OH)2, Al(OH)3, dolomite [CaMg(CO3)2], AlO(OH), silicon nitride, boron nitride, aluminum nitride, silicon carbide, boron carbide, chalk, calcium carbonate, barite, gypsum, hydromagnesite, zeolite, talc, mica, kaolin and wollastonite, aluminosilicate, aluminum silicate, ground glass, glass beads. The filler may optionally be silanized. The filler is preferably Al(OH)3.
[0152] Preferably, the precursor composition of the thermosetting polymer material (A) comprises at least 30 wt% or more, preferably 40 wt% or more, more preferably 50 wt% or more of a filler, preferably an inorganic filler, relative to the total weight of the composition.
[0153] Reagent test kit
[0154] According to a second aspect, the present invention relates to a kit for packaging an article with a nickel-based surface (S), said kit comprising:
[0155] i) a first curable resin composition selected from acrylate resins and methacrylate resins;
[0156] ii) a precursor composition of a thermosetting polymer material (A), wherein the thermosetting polymer material comprises a polymer having the following properties: a Tg lower than or equal to -10°C, a tensile strength after curing of 0.5 to 20 MPa, preferably 1 to 10 MPa, as measured by method ISO 527, and an elongation at break after curing of 5 to 250%, preferably 5 to 100%, as measured by method ISO 527.
[0157] Preferably, the thermosetting polymer material comprises a polymer having a tensile modulus of 10-100 MPa.
[0158] The features and preferences described in detail above for the first curable resin composition and the precursor composition of the thermosetting polymer material (A) also apply to the kit.
[0159] equipment
[0160] According to a third aspect, the present invention relates to a device comprising a packaged article, said device being obtained by implementing the above-described method.
[0161] Specifically, the disclosed method forms an article having a nickel-based surface (S) coated with a layer of a polymer material (P) covering part or all of its surface, and having an encapsulating resin layer of a thermosetting polymer material (A) on top of the polymer material (P). Preferably, there is no direct contact between the article surface and the thermosetting polymer material (A).
[0162] Preferably, the device is a packaged battery.
[0163] Uses of the method of the present invention
[0164] According to another aspect, the present invention also relates to a method for producing an electrical and electronic insulating device, wherein said method comprises at least one step of implementing the method for packaging an article as described in detail above.
[0165] According to another aspect, the present invention relates to the use of a combination of a polymer material (P) as defined in detail above and a thermosetting polymer material (A) as a packaging material for one or more electrical components, in particular batteries, with a nickel-based surface (S), thereby improving the resistance of the packaging assembly to thermal cycles, preventing thermal runaway and heat propagation, and / or reducing mechanical shocks and vibrations.
[0166] Example:
[0167] In the following examples, all contents and percentages are given on a mass basis unless otherwise indicated.
[0168] I-Raw Materials
[0169] - Matrix (S), This is a nickel plated steel commercially available from Tata Steel.
[0170] - Precursor composition of thermosetting polymer material (A):
[0171] Polyol components: CW 30664,
[0172] Isocyanate component, HY 30665: This is a two-component polyurethane system that cures at ambient temperature and contains 66% of a mineral filler commercially available from Huntsman. It is based on a polyether polyol and an aromatic isocyanate. This material is characterized by low-temperature flexibility (Tg = -44°C), high thermal conductivity (1 W / m*K), flame retardancy (UL 94 V0 1mm), and an elongation at break of 15% and a tensile strength of 2 MPa, as measured according to ISO 527.
[0173] - a first curable composition (P), Huntsman 2051 is a 2-component adhesive system that cures at ambient temperature. It is commercially available from Huntsman and is a methyl methacrylate-based polymer. It has a Tg of 127°C, a tensile strength of 40 MPa, and an elongation at break of approximately 10%. The elongation at break and tensile strength are measured according to ISO 527.
[0174] II-Preparing Lap Shear Test Specimens
[0175] Table 1
[0176]
[0177] Before applying the adhesive, the substrate samples were cleaned with isopropyl alcohol. After drying, the substrates were plasma treated for C2, C4, and C6: O2 plasma at 2 mbar and 360 W for 3 minutes.
[0178] For C3 and C4, apply an amount of 2051 of the mixture was added and a second substrate was placed in the apparatus in order to adjust the desired bond thickness of 1.5 mm. The test specimens were cured at 23°C for 24 hours.
[0179] For E1 and E2, apply a thin layer to the substrate with a brush. 2051. Then, cure at 23°C for 15 minutes (the product should be tack-free).
[0180] Then for C1, C2, E1, C5, C6 and E2, apply CW 30664 A mixture of HY30665 (100:7) was applied in an amount to give the bond thickness given in Table 1 and the parts were then cured at 23°C for 24 hours.
[0181] The data in Table 1 are obtained by testing the 100x 25x 1mm The results were obtained using standard test specimens made by overlapping the tapes. The bonding area in each case was 12.5 x 25 mm. The thickness of the adhesive layer was adjusted to 1.5 mm or 0.3 mm (adjusted using glass beads).
[0182] The average lap shear strength of metal-to-metal joints was then tested according to ISO 4587.
[0183] III-Results
[0184] Table 2
[0185]
[0186] AF = Adhesive failure, CF = Cohesive failure
[0187] The results summarized in Table 2 for C1 and C5 show that the polyurethane system The bond was poor and failed in an adhesive failure mode. This result was independent of the bondline thickness.
[0188] C2 and C6 show that plasma treatment does not help to improve the bonding.
[0189] C3 is a comparative test showing that even methyl methacrylate-based adhesives 2051, also can not be well bonded While this resulted in much higher lap shear values, the bond failure was still approximately 50%.
[0190] C4 describes the combination of C3 and plasma. This pretreatment improved the lap shear strength, but the failure mode was still primarily adhesive failure.
[0191] E1 and E2 are examples of the present invention, which demonstrate that Applying the first and subsequent polyurethane layers in direct contact results in a cohesive failure mode predominantly in the polyurethane phase.
Claims
1. A method for encapsulating an article having a nickel-based surface (S) with a thermosetting polymer material (A), said method comprising at least the following steps: i) coating at least a portion of the surface (S) of the article with a first curable resin composition; ii) at least partially curing the first curable resin composition to obtain a nickel-based article coated with a first layer of polymeric material (P); iii) applying at least a precursor composition of a thermosetting polymer material (A) on the first layer of polymer material (P); iv) curing the precursor composition to obtain a top layer of thermosetting polymer material (A), wherein the first curable resin composition is selected from acrylate resins and methacrylate resins, and wherein the thermosetting polymer material (A) comprises a polymer having the following properties: Tg is less than or equal to -10°C, a tensile strength after curing of 0.5-20 MPa, the tensile strength is measured according to method ISO 527, and an elongation at break after curing of 5-250%, the elongation at break is measured according to method ISO 527.
2. The method of claim 1, wherein the nickel-based surface (S) of the article is a solid nickel surface, a nickel-plated surface, or a nickel-covered surface.
3. The method of claim 1 or 2, wherein the first curable resin composition is a two-part composition comprising at least: a) a polymerizable monomer composition comprising an acrylate or methacrylate or a derivative thereof, and b) at least one initiator.
4. The process of claim 3, wherein the polymerizable monomer composition further comprises at least one acid, preferably selected from acrylic acid, methacrylic acid, vinylacetic acid, acryloxypropionic acid, maleic acid and crotonic acid, and / or at least one acid ester, preferably a phosphate ester.
5. The method of any of the preceding claims, wherein the thermosetting polymeric material (A) is a polyurethane, and the precursor composition of the thermosetting polymeric material (A) is a two-part composition comprising at least a) a polyol component and b) an isocyanate component.
6. The method of any one of claims 1 to 4, wherein the thermosetting polymer material (A) is an epoxy resin, and the precursor composition of the thermosetting polymer material (A) is a two-part composition comprising at least a) an epoxy compound and b) a curing agent.
7. The method according to any of the preceding claims, wherein the precursor composition of the thermosetting polymer material (A) further comprises a filler, preferably at least 30 wt% of a filler.
8. The method according to any one of the preceding claims, wherein the precursor composition of the thermosetting polymer material (A) further comprises one or more additives selected from the group consisting of dyes, pigments, flame retardants, softeners, heat aging stabilizers and thixotropy modifiers or rheology modifiers.
9. A method according to any one of the preceding claims, wherein in steps i) and iii), a first curable resin composition and a precursor composition of a thermosetting polymer material (A), respectively, are applied to the surface (S) of the nickel-based article in an amount providing a dry film thickness of 0.1 to 2 mm.
10. The method of any one of the preceding claims, wherein in steps ii) and iv), the first curable resin composition and the second curable resin composition, respectively, are cured at ambient temperature.
11. A kit for packaging an article with a nickel-based surface (S), the kit comprising: i) a first curable resin composition selected from acrylate resins and methacrylate resins; ii) a precursor composition of a thermosetting polymer material (A), said thermosetting polymer material comprising a polymer having the following properties: a Tg lower than or equal to -10°C, a tensile strength after curing of 0.5 to 20 MPa, the tensile strength being measured according to method ISO 527, and an elongation at break after curing of 5 to 250%, the elongation at break being measured according to method ISO 527.
12. A device comprising a packaged article, the device being produced by carrying out the method according to any one of claims 1 to 10.
13. The device of claim 12, wherein the article is selected from batteries having a nickel-based surface.
14. A method for producing an electrical and electronic insulating device, wherein the method comprises at least one step of carrying out the packaging method according to any one of claims 1 to 10.
15. Use of a combination of a polymer material (P) and a thermosetting polymer material (A) for encapsulating an article with a nickel-based surface (S) as defined in any one of claims 1 to 10, thereby improving the resistance of the encapsulated component to thermal cycling, preventing thermal runaway and heat propagation, and / or reducing mechanical shock and vibration.
Citation Information
Patent Citations
method for bonding nickel-based surfaces
DE102017202851A1
Method for improving the adhesion of polymeric adhesives to nickel surfaces
US5532024A